The Spanish Language in America and in Costa Rica According to Dr. Víctor Manuel Sánchez Corrales - Barahona Novoa, Alberto (2014)
This article presents the theoretical foundations used to study Costa Rican Hispanic variety, from the teachings of Professor Victor Manuel Sánchez Corrales. Also, several of his articles on phonetics, morphology and vocabulary in order to highlight the new proposal in our country dialect studies are analyzed. Moreover, the proposed curriculum Dr. Sánchez Corrales outlined to articulate dialect studies in the curriculum of the professionals in Spanish philology.